Beauty and Job Accessibility: New Evidence from a Field Experiment - Weiguang Deng; Dayang Li; Dong Zhou (Global Labor Organization (GLO), 2019)
This study uses a field experiment to resolve the difficulties of quantifying personal appearance and identify a direct causal relationship between appearance and employment in China. The experiment reveals that taste-based pure appearance discrimination exists at the pre-interview stage. There are significant gender-specific heterogeneous effects of education on appearance discrimination: having better educational credentials reduces appearance discrimination among men but not among women. Moreover, attributes of the labor market, companies, and vacancies matter. Beauty premiums are larger in big cities with higher concentrations of women and in male-focused research positions. Similarly, the beauty premium is larger for vacancies with higher remuneration.
Keywords: C93; I21; J71; 330; appearance discrimination; beauty premium; pre-interview stage; field experiment